Association between dental caries lesion presence and previous restorative treatment: epidemiological survey (Arquivos em Odontologia, 2024)
Aim: Dental caries is a biofilm- and sugar-induced disease; therefore, the management of this condition should consider its etiologic factors. Although most clinical trials have focused on operative/restorative techniques to treat dental caries, this approach only addresses the consequences of the disease: the lesions. Thus, this study aimed to evaluate the association between the presence of dental caries lesions as cavities and the presence of previous tooth restorative treatments among adults. Methods: A cross-sectional survey using a database of adults aged 35 – 44 years was conducted. Dental caries lesions were evaluated using the DMFT index (decayed, missing, and filled teeth). The following variables regarding restorative treatment were considered: filled teeth with caries and filled teeth without caries. Multilevel Poisson regression models (fixed effects and random intercepts) were conducted. Results: 9,564 adults were included. The average number of teeth with untreated dental caries (crown) was 1.47. ¼ of adults had one or more filled teeth with dental caries. The presence of one or more teeth with cavitated dental caries lesions (crown) was significantly higher among adults with at least one filled tooth with caries (p < 0.05). This finding was also observed for root caries. Conclusion: The prevalence of teeth with cavitated dental caries lesions (crown and root) was higher among adults who had filled teeth with caries. These findings suggest that patients may have been treated by dentists with a focus on restorative and invasive treatments rather than on addressing the underlying disease, thereby continuing to develop new caries lesions.